Isolated Ventricular Noncompaction Cardiomyopathy Presenting as Fetal Hydrops at 24 Weeks Gestation: A Genomic Analysis. (June 2017) - Armes, Jane E; Squires, Lisa; Lourie, Rohan; Williams, Mark; Gallagher, Renee; Price, Gareth; Stubbs, Andrew; Swagemakers, Sigrid MA; van der Spek, Peter J; Harraway, James; Thomas, Joseph; Venter, Deon J
Ventricular noncompaction cardiomyopathy is a rare form of congenital cardiomyopathy with increasing evidence of genetic etiology, especially when presenting in childhood. Fetal presentation is rare. We describe a case of fetal hydrops, presenting at 24 weeks gestation and leading to intrapartum death at 26 weeks gestation. Autopsy examination revealed characteristic features of left ventricular noncompaction. A genetic analysis identified a constellation of variants of unknown significance in MYH6, TNNC1, and MYBPC3, genes known to be important in sarcomeric function. Additionally, the variant in MYBPC3 was homozygous. While this case did not demonstrate a conventional single-gene mutation as the cause of the ventricular noncompaction, a broader genomic investigation revealed several variants in sarcomeric genes which may act synergistically to impact cardiac function.